OP0030 GRANULOMATOSIS WITH POLYANGIITIS SUSTAINED REMISSION OFF-THERAPY: DATA FROM THE FRENCH VASCULITIS STUDY GROUP REGISTRY. (2nd June 2020) - Puéchal, X.; Iudici, M.; Pagnoux, C.; Karras, A.; Cohen, P.; Maurier, F.; Quéméneur, T.; Lifermann, F.; Hamidou, M.; Mouthon, L.; Terrier, B.; Guillevin, L.
Abstract : Background: Data on granulomatosis with polyangiitis (GPA) sustained remission off-therapy (SROT) are limited and it is unknown whether disease characteristics or treatment regimen may affect it. Objectives: This study aimed to assess SROT of GPA patients from the French Vasculitis Study Group registry, and identify factors associated with its occurrence and durability during follow-up. Methods: GPA had to satisfy the 1990 ACR classification criteria and/or revised Chapel Hill Nomenclature for study inclusion. SROT was defined as remission (BVAS=0) without glucocorticoids (GC) or immunosuppressants (IS), the latter for ≥6 months (ie 2 consecutive visits). SROT and its duration were extracted from the database. Data from patients with 3-, 5- and 10-year SROT were analyzed. Baseline characteristics of patients with 3-year GPA SROT were compared to those of registry GPA patients with available data at 3 years but not in SROT (controls), and 3-year SROT achieving 5-year SROT vs those who relapsed between 3 & 5 years. Patients with 3-year GPA SROT follow-up +7 years were analyzed according to maintained SROT or not. Results: Among 795 database patients with new-onset GPA, 259 achieved at least 1 SROT at some time during their disease, after a median [IQR] of 36 [28–63] months post-diagnosis. The first SROT lasted a median of 14 [I8-32] months. Among 202 of those patients who had follow-up, 73 (36%) remained in SROT for a median follow-up of 34 [14-45] months post-SROT. Among 434 (54%) patients followed for ≥3 years post-diagnosis, 82% had received GC and cyclophosphamide induction therapy. At 3 years post-diagnosis, 92 (21%) patients in SROT were compared to 342 (79%) controls who had relapsed or were still taking GC or IS. Patients achieving 3-year SROT vs controls, respectively, had more frequently received intravenous cyclophosphamide as induction therapy (89% vs 77%, P=0.01), with a higher median number of infusions (7.5 vs 6; P=0.05); no other clinical or biological baseline difference was found. Among those 92 3-year SROT patients, 74 had ≥2 years of additional follow-up: 46 (62%) attained 5-year SROT and 28 (38%) had relapsed after a mean follow-up of 13 months. Baseline clinical and biological characteristics of patients achieving 5-year SROT did not differ from those of 3-year SROT patients who relapsed. Among those 92 3-year SROT patients, 16 had ≥7 additional years of follow-up: 6 (38%) achieved 10-year SROT, ie 8% of 75 GPA with available data at 10 years, and 10 (63%) had relapsed a mean 35 ± 28 months after achieving 3-year SROT. Conclusion: Only 8% of GPA patients achieved 10-year SROT after conventional induction and maintenance therapies. No baseline clinical or biological characteristics helped distinguish patients achieving or maintaining SROT and those who relapsed. However, patients achieving 3-year SROT had received more intensive induction therapy than those who relapsed or were still on GC or IS at 3 years. Disclosure of Interests: None declared